2010
DOI: 10.1002/rcm.4416
|View full text |Cite
|
Sign up to set email alerts
|

Fast and automated characterization of major constituents in rat biofluid after oral administration of Abelmoschus manihot extract using ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry and MetaboLynx

Abstract: In drug metabolism research, the setting up of a complex series of mass spectrometry experiments and the subsequent analysis of the large amounts of data produced are often time-consuming. In this paper, we describe a strategy using ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC/QTOFMS) with automated data analysis software (MetaboLynx) for fast analysis of the metabolic profile of flavonoids in Abelmoschus manihot. Rat plasma and urine samples collected 1 h and 0-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Hydrolysis, hydroxylation, and acetylation were the major metabolic pathways in human and rat intestinal bacteria, (52,53) whereas methylation and glucuronidation were the major metabolic pathways after the absorption of flavonoids in the rat gastrointestinal tract. (15) The most important metabolites in rat blood and urine were quercetin and gossypetin, mainly derived from hibifolin, hyperoside, isoquercetin, and quercetin-3'-O-glucoside. (15) Hyperoside, isoquercitrin, and quercetin monoglucuronide were also identifi ed in rat kidney blood.…”
Section: Sensitivity Analysis (Excluding Rcts In Which Patients Had Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis, hydroxylation, and acetylation were the major metabolic pathways in human and rat intestinal bacteria, (52,53) whereas methylation and glucuronidation were the major metabolic pathways after the absorption of flavonoids in the rat gastrointestinal tract. (15) The most important metabolites in rat blood and urine were quercetin and gossypetin, mainly derived from hibifolin, hyperoside, isoquercetin, and quercetin-3'-O-glucoside. (15) Hyperoside, isoquercitrin, and quercetin monoglucuronide were also identifi ed in rat kidney blood.…”
Section: Sensitivity Analysis (Excluding Rcts In Which Patients Had Wmentioning
confidence: 99%
“…(15) The most important metabolites in rat blood and urine were quercetin and gossypetin, mainly derived from hibifolin, hyperoside, isoquercetin, and quercetin-3'-O-glucoside. (15) Hyperoside, isoquercitrin, and quercetin monoglucuronide were also identifi ed in rat kidney blood. (54) These potentially bioactive constituents in vivo could help clarify the efficacy and safety profiles of this herb as well as potential mechanism of its effects.…”
Section: Sensitivity Analysis (Excluding Rcts In Which Patients Had Wmentioning
confidence: 99%
“…Previous studies in our laboratory have demonstrated that a total of 16 and 38 metabolites were identified in plasma and urine, respectively [20]. There have been reports about the determination of flavonols in rat plasma and urine after oral administration of A. manihot extract [21].…”
Section: Introductionmentioning
confidence: 96%
“…In our previous report, flavonoid glucuronide-sulfate conjugates of A. manihot flavonoid were identified in rat plasma and urine (Guo et al, 2010; Figure 1). In recent years, there has been a growing interest in the biological function of flavonoid glucuronide-sulfate conjugates (Galindo et al, 2012;Shimoi et al, 2001;Terao et al, 2011;Yoshino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%